Análisis bibliométrico de las tesis de pregrado y postgrado realizadas en Bogotá, sobre la implementación y evaluación de programas de terapia y modificación del comportamiento (2005)
The objective of this investigation was to carry out a bibliometric analysis of the pre graduate and post graduate theses about behavior therapy and behavior modification, which had been concluded until the year 2003 (included) in the universities of the city of Bogotá (capital of Colombia) that offered the career of Psychology. With this purpose they were analyzed on the basis of the following variables: to) number of theses found per decade, b) theses number for director, c) number of theses for each one of the implemented behavior therapy and modification techniques and programs, d) number of theses for each one of the problems that was approached by these theses, e) theses number per decade corresponding to each one of the implemented techniques and programs and f) theses number per decade belonging to each one of the problems that was approached. In total 119 theses corresponding to eight universities of the city were analyzed, which involved 30 therapeutic techniques or programs and 50 problems approached through this techniques or programs. The results were discussed in terms of the evolution that has exhibited the behavior therapy and behavior modification approach during the studied period.